Did the repeated debt ceiling controversies embed default risk in US Treasury securities? - Liu, Pu; Shao, Yingying; Yeager, Timothy J. (Journal of Banking & Finance, 2009)
We examine whether the financial market charged a default risk premium to US Treasury securities when the US Federal government repeatedly reached the legally binding debt limits between 2002 and 2006. We show that for the first two of the four recurrences since the first episode in 1996, the financial market charged a small default risk premium to the Treasury securities. However, we find no significant evidence of a pricing effect in the last two recurrences. The results suggest that the financial market gradually perceived the budget standoffs as the boy who cried wolf.